Decreased ultra-processed food consumption as a mediator for lowering cardiovascular risk after a lifestyle program in pediatric obesity: a randomized clinical trial - Ojeda-Rodríguez, Ana; López-Gil, José Francisco; Catalán-Lambán, Ana; Azcona, M. Cristina; Marti del Moral, Amelia (Frontiers in Nutrition, 2026)
IntroductionWe conducted this study to assess changes in cardiovascular health, ultra-processed food (UPF) consumption, and their relationship after a weight loss program intervention in a pediatric population with abdominal obesity.MethodsA total of 107 participants (7–16 years old) were randomly assigned to either the intervention (moderate hypocaloric Mediterranean diet; n = 81) or usual care group (standard pediatric advice; n = 26) for an intensive 8-week lifestyle intervention (ClinicalTrials.gov, Identifier: NCT03147261). UPFs were categorized using the NOVA classification system, and cardiovascular health was defined using the American Heart Association’s Life’s Essential 8 scores (LE8, 0–100 points).ResultsA significant increase in 5.94 points of LE8 (p < 0.001) was observed in the intervention group after the intensive phase, but not in the usual care group. The difference between groups was significant, amounting 8.41 points (p < 0.001). Additionally, both groups reduced their UPF consumption in 2.74 (p < 0.001) and 2.15 portions/day (p < 0.001), with the intervention group showing a greater reduction of −0.59 portions/day (p = 0.032). A significant negative association between changes in UPF consumption and changes in LE8 was found (p = 0.024) after adjusting for changes in energy intake and somatic maturity. Mediation analysis revealed that the effect of the lifestyle program on LE8 score was mediated by the decrease in UPF consumption.ConclusionThe weight loss program in a pediatric population with abdominal obesity not only improved anthropometric and clinical parameters but also reduced UPF consumption, thereby enhancing cardiovascular health.